Pengembangan Profesionalisme Pendidik: Tinjauan pada Perspektif Guru Taman Kanak-Kanak - Rohita; Sofia Hartati; Nurbiana Dhieni (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Professional development is mandatory for educators who have completed their educational qualifications. This aims to ensure that educators can continue to improve their knowledge and skills by changing times, which, of course, have an influence on the world of education. The research aims to analyze professional development at the educator level for kindergarten-age children. Quantitative approach with a cross-sectional survey design type. Data collection was carried out by distributing questionnaires in form. The research subjects consisted of 43 respondents. Data analysis was carried out using statistics. The research results show that of the various types of professional development programs, many teachers participate in training, workshops, educational conferences, and seminars. These two types of programs fulfill a lot of knowledge and skills. Even though teachers have obstacles in developing professionalism, such as time, funds, and suitability of training materials to their needs, they still try to do it with their desires. Support from education unit leaders and the impact on their competencies felt after participating in the development program are other factors in implementing the development of educational professionalism. The implication is that professional development program organizers need to carefully consider various things so that more educators can participate in the programs provided, including analyzing the knowledge and skills teachers need.